Comparing strategies for magnetic functionalisation of microbubbles - Beguin, E; Bau, L; Shrivastava, S; Stride, E (American Chemical Society, 2018)
The advancement of ultrasound-mediated therapy has stimulated the development of drug-loaded microbubble agents that can be targeted to a region of interest through an applied magnetic field prior to ultrasound activation. The need to incorporate therapeutic molecules while optimising responsiveness to both magnetic and acoustic fields, and maintaining adequate stability, however, poses a considerable challenge for microbubble synthesis. The aim of this study was to evaluate three different methods for incorporating iron oxide nanoparticles (IONPs) into phospholipid coated microbubbles using: (1) hydrophobic IONPs within an oil layer below the microbubble shell, (2) phospholipid-stabilised IONPs within the shell, or (3) hydrophilic IONPs non-covalently bound to the surface of the microbubble. All microbubbles exhibited similar acoustic emissions at 1 and 7 MHz. The half-life of microbubbles was found to be more than doubled with the addition of IONPs using both the surface and phospholipid-mediated loading methods, provided the lipid used to coat the IONPs was the same as that constituting the microbubble shell. The highest loading of IONPs per microbubble was also achieved with the surface loading method and the microbubbles were correspondingly most responsive to an applied magnetic field with a three-fold increase in retained microbubbles compared to other groups. For the purpose of drug delivery, the surface loading of IONPs could prevent the further use of the microbubble shell as attachment points for hydrophilic drugs, while hydrophobic drugs could still be incorporated within the shell. In contrast, although the incorporation of phospholipid IONPs produced weakly magnetic microbubbles, it would not interfere with hydrophilic drug loading on the surface of the microbubble.